Management of supplies and movements of tank containers in chemical logistics - KARIMI, I. (Institutional Knowledge at Singapore Management University, 2005)
Effective logistics is the key to improving supply chain performance. Tank containers are attractive from the viewpoints of safety, cost, and environment, and are widely used for transporting fluid chemicals. Minimizing the logistics costs arising from the container flow imbalances across the globe and container cleaning is a major issue that chemical companies and affiliated third-party logistics firms face routinely. In contrast to dry containers, this important problem of managing tank containers in global chemical logistics has received no attention. In this paper, we present an innovative, event-based, "pull" approach for the minimum-cost or the maximum-profit scheduling of the transport and cleaning of multi-product tank containers (loaded and empty) given a set of projected shipment orders. We develop and illustrate through examples a novel linear programming formulation that successfully solves large, industrially relevant problems.